CCR5 is a novel target for the treatment of experimental alopecia areata. Issue 2 (22nd January 2020) - Ito, Taisuke; Suzuki, Takahiro; Funakoshi, Atsuko; Fujiyama, Toshiharu; Tokura, Yoshiki
Abstract: Background: Alopecia areata (AA) is an organ‐specific and cell‐mediated autoimmune disease. Hair follicle autoantigens are disclosed to these autoreactive NKG2D + CD8 + T cells. A Th1 chemokine, CXCL10, is highly expressed on hair follicle keratinocytes and leads to the infiltration of CXCR3 + and CCR5 + Th1 or Tc1 cells around anagen hair follicles in AA lesions. Aim: To evaluate CCR5 as a new candidate target for the treatment of experimental AA. Methods: We initiated 7‐month‐old female C3H/HeJ mice with intracutaneous injections of lymph node (LN) cells, which were activated by IL‐2, IL‐7, IL‐15, and CD3/CD25 Dynabeads, from C3H/HeJ mice with spontaneous AA. Then, 330 μg/d of maraviroc, a negative allosteric modulator of the CCR5 receptor that is already used for treating patients with human immunodeficiency virus, was orally administrated for 28 days. Results: We successfully treated the experimental AA lesions of C3H/HeJ mice with maraviroc. In addition, CCR5 blockade prevented the development of AA in activated T cell‐transferred C3H/HeJ mice. Interestingly, maraviroc‐treated C3H/HeJ mice with experimental AA showed improvement of hair loss lesions after 2 weeks. Immunohistological assessments and FACS analysis revealed a decreased number of CD4 + CCR5 + and CD8 + CCR5 + T cells in the lesions after maraviroc treatment. A real‐time horizontal chemotaxis assay showed that maraviroc significantly inhibited the chemotactic activity of CD8 + LN cells toward RANTES. Furthermore, CCR5 blockade prevented experimental AA development when compared to phosphate‐buffered saline. Conclusion: CCR5 appears to be a promising new candidate target for the treatment of AA. CCR5 blockade may prevent the development of AA as well as improve AA lesions. Abstract : CCR5 blockade effectively improves and prevents alopecia areata in C3H/HeJ mouse. CCR5 inhibitor, maraviroc, is new candidate for the treatment of alopecia areata.